AI IN MODERN PRINTING DESIGN AND PRODUCTION - Bhilare, Meghana; Balkhande, Balasaheb; Pradhan, Indira Priyadarsani; Makhija, Himanshu; Selvi M; Garg, Avni (ShodhKosh: Journal of Visual and Performing Arts, 2025)
With the adoption of Artificial Intelligence (AI) into the contemporary printing designing and printing processes, the conventional processes involved in the printing industry have approached novel avenues of creativity, efficiency, and precision, unlike before. In the past, printing has been developed and transformed by the manual process of printing such as the letter press and lithography to entirely automated digital printing. Nowadays, AI is the next big thing that transforms the design and production stages. In design, AI-based tools can be used to generate concepts automatically, dynamically customize, and identify patterns to ensure that designers can produce visual outcomes that are highly customized and attractive as quickly as possible. Machine learning algorithms can make the colors matching, the patterns more efficient, and the layouts more balanced, whereas generative AI makes it possible to create original and adaptive designs to meet the requirements of a particular audience or a particular branding. In manufacturing, AI tools like predictive maintenance, automated quality control, and real-time defect detection guarantee the consistency of the output quality without causing much downtime and wastage of materials. Also, AI-based smart ink management systems and material utilization systems use AI to maximize material use and sustainability. The advantages of AI integration are felt throughout the printing value chain- creation of operational efficiency, minimization of costs, and accuracy, as well as availability of more personalizations to the customers. Nonetheless, issues like implementation expenses, risks in data privacy, Intellectual property and requirement of skilled manpower is still a major obstacle to complete implementation.